1979
DOI: 10.1007/bf00233653
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of three-dimensional structures derived from isolated hog thyroid cells in primary culture

Abstract: When cultured in polystyrene dishes subjected to previous treatment and supplied with a serum-containing medium, hog thyroid cells form monolayers displaying dome-like arrangements after three to four days. Cells involved in formation of "domes" are morphologically polarized; the apical microvilli of these cells point toward the culture medium. When the tissue is cultured in untreated polystyrene dishes, thyroid cells remain in suspension; their aggregates swell progressively and form hollow spheres encompasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
2

Year Published

1980
1980
2001
2001

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(55 citation statements)
references
References 31 publications
0
53
2
Order By: Relevance
“…Cells were isolated from thyroid glands of adult hogs by a modified [6] discontinuous trypsinization procedure [7]. The Eagle minimum essential medium used was buffered at pH 7.4 and supplemented with 10% newborn calf serum and contained 200 units/ml penicillin, 50 pU/ml streptomycine sulfate and 0.25% (w/v) gelatin [8].…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Cells were isolated from thyroid glands of adult hogs by a modified [6] discontinuous trypsinization procedure [7]. The Eagle minimum essential medium used was buffered at pH 7.4 and supplemented with 10% newborn calf serum and contained 200 units/ml penicillin, 50 pU/ml streptomycine sulfate and 0.25% (w/v) gelatin [8].…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…Preliminary experiments showed that the factor present in the supematant was heat stable and dialyzab~e. Thus the increased responsiveness of the adenyiate cyclase system to TSH (positive regulation) observed when thyroid cells are cultured with O-100 @J/ml TSH ( [2,3], table 1) might be associated with modulation of the intrace~u~r GTP level by the hormone. An estimate of -1 mM for the intracellular GTP concentration in TSH-treated cells can be derived from data of the type described in table 2 if we assume that the concentration of free GTP in the homogenate is 10 PM on the basis of the identical effect obtained on TSH striation of the 104 X g fraction by addition of the lo5 X g supernatant or 10 ,uM GTP and using 4 pl/mg protein for the cell volume [ 151.…”
Section: S Basal and Stimulated Adenylate Cyclase Aandiv@ Of I O4 X Gmentioning
confidence: 99%
“…In addition to its action on the inhibition of cAMP synthesis by adrenergic [9], muscarinic cholinergic agonists [6][7][8][9][10][11][12][13] and opiates [6,14] Na ÷ appears to have divergent effects on adenylate cyclase activities depending on the biological system studied. In the porcine kidney medulla, Na ÷ was required for full expression of stimulation by vasopressin [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid epithelial cells were obtained from porcine thyroid glands by a discontinuous trypsin-EGTA treatment [11 ]. Freshly isolated ceils were suspended at 2 X 106 cells/ml in Eagle minimum essential medium supplemented with newborn calf serum (10%, v/v), gelatin (0.25%) and TSH (0.1 mU/ml) unless otherwise mentioned.…”
Section: Cell Culture and Membrane Preparationmentioning
confidence: 99%
See 1 more Smart Citation